Psoriasis :coping with social stigma - Magdoline, Luhok. (UNIMAS, 2010)
A qualitative study of individuals living with psoriasis has been conducted in Tuaran District, Sabah.It aimedin exploring the experience of being stigmatized, describing the coping strategies used and it effectiveness in dealing with social stigma. With in-depth interview to nine participants in this qualitative research, it is found that stigmatization was triggered by the visibility of the disease –marked by visibility; to cope with this stigmatization, they tended to hide and conceal it -the act of concealment; they tried to avoid the public and preferred being alone; developed feeling of anger and self-blaming; telling self “I don’t care”; and find source of support. With the coping strategies, these give them the feelings of belonging; making adjustment and changes in self. Through this study, it suggests nurses to imply holistic and spiritual nursing in caring for individuals with psoriasis. Whilst for the society, this study creates awareness and understanding in the social stigma that have experienced by individuals with psoriasis, thus bringing them back to the society.